Clinical predictors of functional recovery at six month post-stroke - Gbiri, Caleb Ademola; Akinpleu, Aderonke Omobonike; Ogunniyi, Adesola; Akinwuntan, Abiodun E; Van Staden, C Werdie (Asian Journal of Medical Sciences, 2014)
Aim: To investigate predictors of functional recovery at six-month among Nigerians with first-ever stroke. Methods: Participants with first ever stroke were recruited at stroke?onset from the University College Hospital, Ibadan, Nigeria. Stroke severity was measured using the National Institute of Health Stroke-Scale. Stroke was classified using the results of the CT scan of the brain. The weighted-standard values of Barthel Index and Frenchay Activities Index were combined to indicate Comprehensive Activities of Daily Living (CADL). The presence of depressive features and Trunk-Control (TC) were measured using the Centre for Epidemiological Scale-Depression and the Postural Assessment-Scale for Stroke?Patients respectively. Measurements were taken every month for six months. Data were analyzed using multivariate regression and survival analyses at p=0.05. Results: Sixty?five participants were recruited. Ten died within a week of stroke onset. Fifty-five (mean age = 57.4±14.8 years, 28 males) participants completed the study; Twenty-six (47.3%) had ischaemic stroke and 29 (52.7%) had haemorrhagic stroke. Forty of the 55 participants were married and of the 40, 31 reported spousal support. Type of stroke (β=7.5) and age (β=–0.4) significantly predicted functional recovery after controlling for co-morbidity (β=–2.1), brainstem lesion (β= –0.2), stroke severity (β= –0.6) and TC (β= 0.7) and the scores on depressive symptoms ratings (β= –0.1). Conclusion: Functional recovery at six?month is better in individuals who had haemorrhagic stroke. However, functional recovery decreases as age increases. The combination of haemorrhagic stroke with the presence of co-morbidity predicted death after stroke. DOI: http://dx.doi.org/10.3126/ajms.v6i1.5911 Asian Journal of Medical Sciences Vol.6(1) 2015 49-54